Teaching writing: theories and practices - Tarvers, Josephine Koster (HarperCollins, 1992)
Includes bibliographical references and index; 3 parts: Perceiving theory; practicing theory (Organizing a writing class; conducting classes; designing writing assighments;...); resources for writing teachers